Experimental turbulence studies for gyro-kinetic code validation using advanced microwave diagnostics. (21st July 2015) - Stroth, U.; Bañón Navarro, A.; Conway, G.D.; Görler, T.; Happel, T.; Hennequin, P.; Lechte, C.; Manz, P.; Simon, P.; Biancalani, A.; Blanco, E.; Bottereau, C.; et al.
Abstract: For a comprehensive comparison with theoretical models and advanced numerical turbulence simulations, a large spectrum of fluctuation parameters was measured on the devices ASDEX Upgrade, TCV, and Tore-Supra. Radial profiles of scale-resolved turbulence levels in H-mode discharges are measured and compared with GENE simulations in the transition range from ion-temperature-gradient to trapped-electron-mode turbulence. Correlation reflectometry is used to study the microscopic structure of turbulence and GAMs in discharges where poloidal flow damping was varied by means of variations of the shape of the poloidal plasma cross-section and collisionality. Full-wave codes and synthetic diagnostics are applied for the interpretation of the data.